IDENTIFIKASI DAN UJI POTENSI KAPANG LIPOLITIK SEBAGAI PEMBELAJARAN IKUIRI - Ervina Mukharomah (Bioilmi: Jurnal Pendidikan, 2017)
This study aims to invite students to dig up information around them. So that students can reveal the information obtained by doing experiments with inquiry learning. This research has been done in 2016 in Unsri labolatorium, the result of this research found that there are 8 isolates of mold. Isolate V1 has the same characteristic as V8, isolate V2 has the same characteristics as V3, V6 and V7, whereas the isolate V4 has the same characteristic as V5. Therefore, based on the identification result, it is stated that the isolates of V1 with V8 are Aspergilus fumigatus, hereinafter called Aspergilus fumigatus (V1). Isolates of mold V2, V3, V6 and V7 are Cylindrocladium sp hereinafter called Cylindrocladium sp (V2). Isolates of mold V4 and V5 are the same isolate and identified as Fumago sp hereinafter called Fumago sp (V4).